20(S)-Protopanaxadiol Inhibits Angiotensin II-Induced Epithelial- Mesenchymal Transition by Downregulating SIRT1 - Wang, Yuchen; Xu, Huali; Fu, Wenwen; Lu, Zeyuan; Guo, Minyu; Wu, Xueji; Sun, Mingyang; Liu, Yanzhe; Yu, Xiaofeng; Sui, Dayun (Frontiers in Pharmacology, 2019)
20(S)-Protopanaxadiol (PPD) is one of the major active metabolites in ginseng saponin. Our previous studies revealed a broad spectrum of antitumor effects of PPD. Angiotensin II (Ang II), the biologically active peptide of the renin-angiotensin system (RAS), plays a critical role in the metastasis of various cancers. However, its role in the anti-metastatic effects of PPD is not clearly understood. In this study, we investigated the inhibitory effect of PPD on Ang II-induced epithelial-mesenchymal transition (EMT) in non-small cell lung cancer (NSCLC) cells, and the potential molecular mechanisms of suppression of NSCLC migration and metastasis by PPD. Treatment of A549 cells with Ang II increased metastases in an experimental model of cancer metastasis in vivo. PPD effectively prevented Ang II-induced EMT, as indicated by upregulation of E-cadherin and downregulation of vimentin. Additionally, Ang II upregulated the class III deacetylase sirtuin 1 (SIRT1) expression in EMT progression, while downregulation of SIRT1 was involved in suppression of Ang II-induced EMT by PPD. Moreover, the inhibitory effect of PPD was reversed by SIRT1 upregulation, and PPD demonstrated synergy with an SIRT1 inhibitor on Ang II-induced EMT. Taken together, our data reveal the mechanism of the anti-metastatic effects of PPD on Ang II-induced EMT and indicate that PPD can be used as an effective anti-tumor treatment.